2021
DOI: 10.1091/mbc.e19-08-0436
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the electrostatic profiles of cellular membranes

Abstract: Anionic phospholipids can confer a net negative charge to biological membranes. This surface charge generates an electrical field that serves to recruit extrinsic cationic proteins, can alter the disposition of transmembrane proteins and causes the local accumulation of soluble counterions, altering the local pH and the concentration of physiologically important ions like calcium. Because the phospholipid composition of the different organellar membranes varies, their surface charge is similarly expected to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Reasoning that, with respect to charge, the decreases in the four predominant anionic phospholipids would more than offset any increases in PIP3, we sought to measure spatiotemporal changes in membrane surface charge. We started with a generic membrane surface charge sensor, R(+8)-Pre, which had been quantitatively characterized in vitro (by liposome binding assays) to detect the combination of anionic lipids 22, 30, 54 . Consistent with our observations of the individual lipids, we found that the back-state regions of cortical waves in Dictyostelium cells are defined by high negative surface charge whereas the front-state regions shun the charge sensor (Figure 2A; Video S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasoning that, with respect to charge, the decreases in the four predominant anionic phospholipids would more than offset any increases in PIP3, we sought to measure spatiotemporal changes in membrane surface charge. We started with a generic membrane surface charge sensor, R(+8)-Pre, which had been quantitatively characterized in vitro (by liposome binding assays) to detect the combination of anionic lipids 22, 30, 54 . Consistent with our observations of the individual lipids, we found that the back-state regions of cortical waves in Dictyostelium cells are defined by high negative surface charge whereas the front-state regions shun the charge sensor (Figure 2A; Video S4).…”
Section: Resultsmentioning
confidence: 99%
“…Relatively few studies have focused on the role of membrane surface charge itself 21, 29 . These have proposed that the zeta potential, in the range of −20 to −50 mV 3032 , acts in regulating local pH and soluble second messenger concentrations, altering ion channel conductance, and controlling the association of peripheral membrane proteins 2124, 3336 . It was also shown that the during immune synapse formation and phagocytosis, the membrane surface charge changes 22, 3739 .…”
Section: Introductionmentioning
confidence: 99%
“…This yield is more than three times higher than the yield from ULGT agarose, HGT agarose, and PVA. This result is notable since ULGT agarose and PVA, both used extensively in the literature [32][33][34][35][36][37][38][39][40] , produce significantly lower yields of GUVs in PBS compared to LGT agarose. ULGT and LGT agaroses with different catalog numbers showed similar yields to those shown in Figure 2 (Figure S4).…”
Section: Low Gelling Temperature Agarose Produces the Highest Yield O...mentioning
confidence: 99%
“…The idea of localisation controlling the function and activity of PM resident proteins is well-established (Eisenberg et al, 2021; Kusumi et al, 2005, 2010, 2011; Trimble and Grinstein, 2015). Our work provides a link between EFR3 (and PI4K-IIIα) and insulin-stimulated glucose transport, establishing EFR3 as a key locus of insulin action.…”
Section: Discussionmentioning
confidence: 99%